'Left to Fend for Themselves': Immigration, Race Relations and the State in Twentieth Century Northern Ireland. Issue 1 (2nd January 2018) - Crangle, Jack
Abstract: Race relations legislation was only introduced to Northern Ireland in 1997, 31 years later than in Britain. This article examines the obstacles and challenges faced by minorities there during the twentieth century. By providing a case study of Northern Ireland, the article shifts the focus away from British inner cities, emphasising that outlying regions – so often overlooked within the context of UK race relations historiography – also had to grapple with issues surrounding race and immigration. The article challenges the notion that Northern Ireland was exclusively white, showing how ethnic minorities there were repeatedly overlooked and excluded.